Morality and Immorality in Politics in Aceh Post 2005 MoU Helsinki (A Case Study on the Relevance of Actions Compared with Peace Promises) - Manan, Abdul; Rasyad, Rasyad; Saputra, Iping Rahmat; Sa’i, Sa’i; Daud, Anwar; Tuffahati, Zulfa; Champion, Ibrahim (Jurnal Ilmiah Peuradeun, 2024)
This research analysed the morality of actions taken to implement promises made in Aceh post-2005 MoU Helsinki Peace Agreement. Consideration has been given to the current political conditions in Aceh. Morality is a product of a culture and differs between cultures: Differences between the morality of the Acehnese and that of the Javanese were a major cause of conflict between the Acehnese and the Government of Indonesia. The immorality of the Indonesian Government's actions has been a major cause of rebellion in Aceh in the past. Field research was done by recording participant observations, after which data analysis used the Miles et al. methods. Results showed that after nearly 2 decades of peace, not all the goals in the MoU have been realized. Yes, there were major improvements—there were no more security operations, and some special institutions have been set up: However, many Acehnese haven't felt the full morality of all the peace promises, and morality could be better amongst the elite in both Aceh and Jakarta.